2018
DOI: 10.1098/rsos.172193
|View full text |Cite
|
Sign up to set email alerts
|

Resurrected ‘ancient’ Daphnia genotypes show reduced thermal stress tolerance compared to modern descendants

Abstract: Understanding how populations adapt to rising temperatures has been a challenge in ecology. Research often evaluates multiple populations to test whether local adaptation to temperature regimes is occurring. Space-for-time substitutions are common, as temporal constraints limit our ability to observe evolutionary responses. We employed a resurrection ecology approach to understand how thermal tolerance has changed in a Daphnia pulicaria population over time. Temperatures experienced by the oldest genotypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…In some cases, historical records of the environment as well as "time capsules" of earlier life do exist. In one such example, "resurrected" resting eggs of ancient Daphnia pulicaria populations collected from sediments when ponds were cooler were used to compare to modern populations when the ponds were warmer (139). Modern D. pulicaria were more heat tolerant and expressed more hsp70 than the ancient population (139).…”
Section: Adjustment (Physiology)mentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, historical records of the environment as well as "time capsules" of earlier life do exist. In one such example, "resurrected" resting eggs of ancient Daphnia pulicaria populations collected from sediments when ponds were cooler were used to compare to modern populations when the ponds were warmer (139). Modern D. pulicaria were more heat tolerant and expressed more hsp70 than the ancient population (139).…”
Section: Adjustment (Physiology)mentioning
confidence: 99%
“…In one such example, "resurrected" resting eggs of ancient Daphnia pulicaria populations collected from sediments when ponds were cooler were used to compare to modern populations when the ponds were warmer (139). Modern D. pulicaria were more heat tolerant and expressed more hsp70 than the ancient population (139). Commonly, a "time for space" convention is used, by which populations that occur in regions that locally differ in climate (e.g., at edge and center of species distributions) are used as a proxy for how one population would respond plastically to change over time.…”
Section: Adjustment (Physiology)mentioning
confidence: 99%
“…2011; Yousey et al. 2018). Similarly, sedimentary archives of marine diatom and dinoflagellate cysts have been utilized to reconstruct records of genetic variation and evolutionary responses to salinity, hydrographic, and temperature variation (Härnström et al.…”
Section: Introductionmentioning
confidence: 99%
“…Such interference with genetic adaptation has been found in many studies reporting within-generation plasticity (Gienapp et al, 2008; Merilä and Hendry, 2014), but the transgenerational mechanism found here is much less documented. Transgenerational effects may be difficult to detect: though the resurrection ecology approach is among the most powerful methods to study adaptation to climate change (Lenormand et al, 2018; Nogués-Bravo et al, 2018; Orsini et al, 2013; Weider et al, 2018), without crosses we would have concluded that genetic adaptation had taken place (as in Geerts et al, 2015; Yousey et al, 2018). Compared to other studies, our adaptive transgenerational effects are large (Jeremias et al, 2018; Sánchez‐Tójar et al, 2020; Yin et al, 2019), and contrast strikingly with the absence of adaptive genetic and within-generation plastic effects, providing an example where adaptation involves traits whose heritability is entirely “missing” (Trerotola et al, 2015).…”
Section: Discussionmentioning
confidence: 99%